2021
DOI: 10.7150/thno.49672
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal photobiomodulation treatment on neonatal hypoxic ischemia in rat offspring

Abstract: Neonatal hypoxic-ischemic (HI) injury is a severe complication often leading to neonatal death and long-term neurobehavioral deficits in children. Currently, the only treatment option available for neonatal HI injury is therapeutic hypothermia. However, the necessary specialized equipment, possible adverse side effects, and limited effectiveness of this therapy creates an urgent need for the development of new HI treatment methods. Photobiomodulation (PBM) has been shown to be neuroprotective against multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 132 publications
(139 reference statements)
2
47
0
Order By: Relevance
“…The Barnes maze task was performed to measure hippocampus-dependent spatial learning and memory following our previously published procedures 28 . The Barnes maze used in our study consists of a circular platform (100 cm high) with 18 holes around the circumference.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Barnes maze task was performed to measure hippocampus-dependent spatial learning and memory following our previously published procedures 28 . The Barnes maze used in our study consists of a circular platform (100 cm high) with 18 holes around the circumference.…”
Section: Methodsmentioning
confidence: 99%
“…All fluorescent images were analyzed using ImageJ software (Version 1.49, NIH, Bethesda, MD, USA) or Imaris software (Bitplane AG, Zürich, Switzerland). 3D reconstruction was performed using Imaris software following the instructions described in previous studies 28 , 31 . The smoothing was set at 0.4 μm for all images and channels.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PBM has been used clinically for more than 50 years and studied in various diseases and conditions, such as muscle [ 5 ], wound healing [ 6 ], pain relief [ 7 ], arthritis [ 8 ], hair loss [ 9 ], orthodontic mini-implant stability [ 10 ], neurodegenerative diseases [ 11 ] and most recently in COVID-19 patients [ 12 ]. PBM has been shown over decades to be a patient-directed, adjunctive, effective, non-invasive, and safe treatment option to mitigate mitochondrial dysfunction [ 13 ], oxidative stress [ 14 , 15 ], inflammatory conditions [ 16 ], and, more recently, gut microbiota dysbiosis [ 17 ], which are all primary contributors to CKD. Notably, several studies have demonstrated a positive effect of PBM in different models of kidney diseases, including acute kidney injury, glomerulonephritis, and metabolic syndrome-related kidney injury [ 18 ].…”
Section: Introductionmentioning
confidence: 99%